Mathematics Communication Skill of Students on Project Blended Learning (PB2L) with Moodle - Marliani, Lia Marliani Lia; Waluya, S. B.; Cahyono, E. (Universitas Negeri Semarang, 2021)
This research aims to analyse effectiveness of Project Based Blended Learning (PB2L) to mathematics communication skill of students and to describe the skill on PB2L learning with moodle. This mixed method research with sequential explanatory design took XMIPA of SMA N Garawangi, Kuningan, in academic year 2018/2019 as the population. The subjects consisted of 33 XMIPA4 students. The techniques of collecting data were test, observation, documentation, and interview. Based on the findings, the mathematics communication skill on PB2L with moodle was effective. Students with poor mathematics communication skill consisted of 2 persons, the moderate students consisted of 24 persons, while the high category students consisted of 7 persons.